Search for associations of polymorphic variants of the MTHFR, MET, CHEK2 genes, identified through next-generation sequencing, with cervical cancer - K. V. Lenkova; R. M. Minyazeva; V. L. Akhmetova; I. R. Gilyazova; R. I. Khusainova; I. R. Minniakhmetov (Успехи молекулярной онкологии)
Introduction. Worldwide, cervical cancer is the 4th most common cancer in women, and morbidity continues to grow. Supposedly, development of human papilloma virus-associated cervical cancer depends on genetic and epigenetic factors, but molecular pathogenesis of this pathology has not yet been established. Recently obtained data show that germline substitutions not only increase the risk of cancer but also affect tumor progression and form the picture of somatic changes in this malignant neoplasm.Aim. To investigate germline variants of the MTHFR, MET and CHEK2 genes and evaluate their significance in development of genetic predisposition towards cervical cancer.Materials and methods. DNA of 108 women with cervical cancer was analyzed. The comparison group included 51 patients with human papilloma virus elimination and 333 relatively healthy women. In the patient cohort, an analysis was performed using next-generation sequencing (NGS) and a custom panel aimed at genes participating in tumor designed by us. Additionally, clinical significance of the identified substitutions was evaluated using literature data, databases and bioinformatics methods. Additional association studies were performed for с.677С>Т and с.1298A>C variants of the MTHFR gene, c.2962C>T variant of the MET gene, с.972G>C variant of the CHEK2 gene.Results. It was observed that polymorphic variants с.972G>C and c.1312С>A of the CHEK2 gene have pathogenic potential. Among 11 substitutions in the MET gene identified during the study, variants c.2962C>T, c.2975C>T and c.3895G>C are liable to be pathogenic. Correlations between T locus allele c.2962C>T of the MET gene (p = 0.002; χ2 = 9.8) and C locus allele с.972G>C of the CHEK2 gene (p = 0.05; χ2 = 3.8) with the risk of cervical cancer development were found.Conclusion. During the study, a group of germline substitutions in the MTHFR, MET and CHEK2 genes with unclear clinical significance was identified. It was shown that substitutions с.972G>C and c.1312С>A in the CHEK2 gene and c.2962C>T, c.2975C>T, c.3895G>C in the MET gene have pathogenic potential in the context of cervical cancer. Additionally, previously unknown associations between loci c.2962C>T of the MET gene and с.972G>C of the CHEK2 gene with this pathology were described.